Increasing the catalytic stability of microporous Zn/ZSM-5 with copper for enhanced propane aromatization - G.G. Oseke (Elsevier, 2021)
Catalytic transformation of light alkanes to aromatic compounds which are feedstocks to petrochemical industries is an important process. Here, a simple method of co-impregnation was employed to synthesize Zn-Cu/ZSM-5 for propane aromatization. Copper of varying loading 1–3 wt% was co-impregnated with zinc to improve zinc stability at the reaction condition. Catalyst physicochemical properties were analyzed using XRD, BET, N2-adsorption, FTIR, FTIR-Pyridine, SEM, TEM, H2-TPR and XPS. The XRD and FTIR characterization showed that the modified catalysts retained their crystallinity after metal impregnation with the XPS confirming the metal species having oxidation state of 2+. Hydrogen-TPR and XPS change in reduction temperature and binding energy spectra showed stronger intermetallic interaction respectively. Incorporation of Cu with Zn on ZSM-5 reduced Bronsted acidity from the FTIR-Pyridine while N2-adsorption isotherms verified the catalyst are microporous. The performance tests for propane aromatization over synthesized catalysts were carried out in a fixed bed reactor using GHSV of 1200 ml/g-h at 540 °C and atmospheric pressure. Co-impregnation of Zn with Cu improved the catalytic activity and sustained aromatic selectivity at an average of 85% for 12 h’ time on stream as compared to HZSM-5 (10%) and Zn/ZSM-5 (50%). Product distribution showed reduced light hydrocarbon formation and increased aromatic compounds with high selectivity towards toluene, m and o-xylene among the aromatic product distribution. The best aromatic selectivity product distribution was recorded for 2 wt% Cu with Zn, thus a more stable catalyst developed. XPS and H2-TPR analysis showed that the synergistic interaction between the two metals (Cu and Zn) improved the performance of bimetallic Zn-Cu/ZSM-5 catalyst by promoting zinc dispersion and stability during reaction.